The UNC-Wisconsin Rhesus Macaque Neurodevelopment Database: A Structural MRI and DTI Database of Early Postnatal Development - Young, Jeffrey T.; Shi, Yundi; Niethammer, Marc; Grauer, Michael; Coe, Christopher L.; Lubach, Gabriele R.; Davis, Bradley; Budin, Francois; Knickmeyer, Rebecca C.; Alexander, Andrew L.; Styner, Martin A. (Frontiers in Neuroscience, 2017)
Rhesus macaques are commonly used as a translational animal model in neuroimaging and neurodevelopmental research. In this report, we present longitudinal data from both structural and diffusion MRI images generated on a cohort of 34 typically developing monkeys from two weeks to 36 months of age. All images have been manually skull stripped and are being made freely available via an online repository for use by the research community. Additionally, this database will continue to be updated as we process the data, create atlases, and perform fiber tracking on the DTI data.